Novel fluorine-free halogen-free flame-retardant high-performance PC material and preparation method thereof

By grafting and modifying ultra-high molecular weight polysiloxanes and compounding them with polycarbonate to form a semi-net structure, the problem of existing halogen-free flame-retardant polycarbonate materials relying on fluorine additives is solved, and a completely fluorine-free and halogen-free flame-retardant polycarbonate material is achieved, with excellent mechanical and flame-retardant properties.

CN119899507APending Publication Date: 2025-04-29SHANGHAI PRET COMPOSITES +3
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411923704.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing halogen-free flame-retardant polycarbonate materials rely on fluorine additives, especially polytetrafluoroethylene as anti-drip agents, which cannot fully meet the future demand for fluorine-free and halogen-free materials, and there are environmental and health risks.

Method used

By grafting modification of ultra-high molecular weight polysiloxane, GMA groups are added, and composited with copolymerized polycarbonate and silicon copolymer polycarbonate, a semi-net structure is formed using a high-power extruder process to replace the anti-drip effect of polytetrafluoroethylene.

Benefits of technology

It has achieved a completely fluorine-free and halogen-free flame-retardant polycarbonate material, which has high impact, tensile properties, high temperature and low temperature resistance, meets the flame retardant standards of VO grades, and reduces potential risks to the environment and health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005208693780000021
    Figure BDA0005208693780000021
Patent Text Reader

Abstract

The invention discloses a novel fluoride-free halogen-free flame-retardant high-performance PC material and a preparation method thereof. The novel fluoride-free halogen-free flame-retardant high-performance PC material comprises the following components: 20-80% of copolymerized PC; 20-70% of silicon copolymerized PC (polycarbonate); 1-10% of modified ultrahigh molecular weight polysiloxane; 1-3% of a compound flame retardant; 0.3-5% of a lubricant and 0.5-1% of an initiator. The novel halogen-free flame-retardant PC material completely free of fluorine elements is prepared for the first time, is completely free of fluorine and drips, meets the VO fireproof grade, has high impact resistance and high tensile property, allows a glowing filament to pass 850 DEG C, is good in low temperature resistance and extremely low in internal stress, and adapts to the trend of halogen-free flame-retardant polycarbonate defluorination in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel fluorine-free, halogen-free, flame-retardant, high-performance PC material, in particular to a completely fluorine-free and halogen-free flame-retardant PC material. Background Art

[0002] Polycarbonate is an excellent engineering plastic with many advantages, so it is widely used in modern life and modern industry. Polycarbonate is transparent, high gloss, and has a certain degree of flame retardancy. It can achieve VO grade by adding flame retardants and fluorine-containing anti-drip agents, so it occupies a large market in the application of electronic and electrical products.

[0003] As humans pay more attention to their own health and the environment, people have found that many flame retardants or materials used for flame retardancy are very harmful to human health and the environment. Therefore, many chemical materials used for flame retardant materials are gradually included in the supervision and even banned. In the production and manufacturing application process of flame retardant PC materials, polytetrafluoroethylene needs to be added as an anti-drip agent to reach the VO level of international standards. More importantly, flame retardants containing fluorine elements and polytetrafluoroethylene used as anti-drip have become highly concerned substances and will be banned in the near future. Therefore, fluorine-free and halogen-free flame retardant PC materials have become the darling of the new era and will replace existing fluorine-containing products. From the current point of view, there is no mature fluorine-free flame retardant PC on the market (there are often flame retardant PCs that do not contain PFAS on the market, but they are not fluorine-free. Polytetrafluoroethylene is still added as an anti-drip agent. Polytetrafluoroethylene is not included in the PFAS list for the time being). Therefore, the development of halogen-free flame retardant PC materials that do not contain fluorine flame retardants and polytetrafluoroethylene has become a very important topic and work. The present invention develops a new type of completely fluorine-free flame-retardant polycarbonate material by studying the flame-retardant mechanism of PC and the anti-dripping principle of polytetrafluoroethylene. Summary of the invention

[0004] One of the technical problems to be solved by the present invention is to solve the current dependence of halogen-free flame retardant polycarbonate on fluorine additives, such as fluorine-containing perfluorobutyl sulfonate flame retardants and polytetrafluoroethylene, especially polytetrafluoroethylene anti-drip agent. In recent decades, halogen-free flame retardant polycarbonate must add polytetrafluoroethylene as an anti-drip agent, otherwise it will drip and cannot reach the VO or higher flame retardant level required by internationally recognized standards.

[0005] The second problem to be solved by the present invention is to remove fluorine in halogen-free flame retardant polycarbonate flame retardant materials. In the future, the requirements for fluorine element will become more and more stringent. Currently, the EU REACH regulations have listed PFAS as a substance of high concern, and materials containing fluorine elements will even be banned in the future.

[0006] The technical problem to be solved by the present invention is achieved through the following technical solutions:

[0007] A novel halogen-free and fluorine-free flame-retardant polycarbonate material is composed of the following raw materials in percentage by weight:

[0008]

[0009] The silicon copolymer polycarbonate has a melt index MI of 5-20 g / 10 min.

[0010] The copolymer polycarbonate has a melt index MI of 3-20 g / 10 min.

[0011] The modified ultrahigh molecular weight polysiloxane is prepared by using ultrahigh molecular weight polysiloxane powder with a molecular weight of more than 1 million, and then grafting glycidyl methacrylate GMA to the ultrahigh molecular weight polysiloxane through a specific process to prepare a modified ultrahigh molecular weight polysiloxane with a GMA group.

[0012] The compound flame retardant is a powder obtained by compounding three flame retardants, namely sulfonate, phosphorus nitrogen and silicone, in a specific proportion.

[0013] The lubricant is pentaerythritol stearate, preferably PETS-AP;

[0014] The initiator is a peroxide or azo initiator, preferably Akzo Nobel Perkadox L-W75.

[0015] The preparation method of the novel fluorine-free and halogen-free flame-retardant high-performance PC material comprises the following steps:

[0016] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0017] (1) Add 80-90% by weight of ultra-high molecular weight polysiloxane powder, 10%-20% of glycidyl methacrylate (GMA) and an appropriate amount of initiator into acetone and mix well. Then stir the mixture and let it stand for 4 hours.

[0018] (2) After standing, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0019] (3) After the irradiation is completed, the product is extracted and washed with acetone;

[0020] (4) After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0021] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0022] Step 3: Add copolymer polycarbonate and silicon copolymer polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0023] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0024] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0025] The present invention uses copolymerized PC, silicon copolymerized PC and ultra-high molecular weight polysiloxane as the base material, and first modifies the ultra-high molecular weight polysiloxane, mainly by first grafting a GMA group with high reactivity on the surface of the ultra-high molecular weight polysiloxane, and then adding it to the silicon copolymerized polycarbonate and copolymerized polycarbonate base material in a certain proportion. On the one hand, under the principle of "like dissolves like", the chain-like ultra-high molecular weight polysiloxane can be better dispersed in the silicon copolymerized polycarbonate; on the other hand, under the action of the initiator, the ultra-high molecular weight polysiloxane containing the GMA group can undergo a bridging reaction with the ester group in the polycarbonate; and then, by using a high-power and high-torque twin-screw extruder, the chain-like ultra-high molecular weight polysiloxane can be fiberized during the extrusion process under the action of high speed and high shear force, and at the same time, a semi-net-like structure can be formed under the bridging reaction of the initiator. When the polycarbonate material burns, the semi-network structure formed by the ultra-high molecular weight polysiloxane can inhibit the dripping of the burning products, perfectly replacing polytetrafluoroethylene to achieve the anti-drip effect, and giving the material stable and excellent flame retardancy.

[0026] The present invention prepares for the first time a new type of halogen-free flame-retardant PC material that is completely fluorine-free and drip-free, meets the VO fire protection level, has high impact resistance, high tensile performance, a glow wire that passes 850°C, good low temperature resistance, and a high-performance polycarbonate material with extremely low internal stress, which adapts to the future trend of defluorination of halogen-free flame-retardant polycarbonate.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention breaks through the industry bottleneck that the preparation of halogen-free flame-retardant polycarbonate cannot be separated from polytetrafluoroethylene as an anti-dripping agent. This is because the existing technology requires the addition of polytetrafluoroethylene or other fluorine-based flame retardants to solve the problem of dripping during the combustion process. The present invention adopts other methods and technologies to prepare a new type of halogen-free and fluorine-free flame-retardant high-performance polycarbonate material.

[0029] 2. As fluorine-based materials are gradually banned by European and American laws and regulations, they will definitely be eliminated in the future. The material of the present invention is completely fluorine-free, can meet all current laws and regulations in the world, and has a broader application market. DETAILED DESCRIPTION

[0030] Example 1

[0031] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 77% copolymer polycarbonate; 20% silicon copolymer polycarbonate; 1% modified ultra-high molecular weight polysiloxane; 1% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0032] The copolymer polycarbonate is a medium-high viscosity PC, and its melt index MI is 3-20g / 10min, preferably Wanhua PCA1105, MI=9g / 10min; the silicon copolymer polycarbonate melt index MI=5-25g / 10min, preferably SABIC EXL1414T, MI=9g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.2: 0.3: 0.5; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably benzoyl peroxide from Akzo Nobel, brand Perkadox L-W75.

[0033] The preparation method of the composite material of the present invention:

[0034] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0035] 1. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix evenly, then stir the mixture evenly and let it stand for 4 hours.

[0036] 2. After standing, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0037] 3. After irradiation, the product is extracted and washed with acetone;

[0038] 4. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0039] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0040] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0041] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0042] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0043] project standard Composite material of the present invention Tensile strength MPa GB / T1040 62 Elongation % GB / T1040 77 Bending strength MPa GB / T9341 89 Flexural modulus MPa GB / T9341 2320 Notched impact strength kj / m2 GB / T1843 50 MFRg / 10min GB / T3682 8.7 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.20 Heat Deflection Temperature GB / T1633 124 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV1

[0044] Example 2

[0045] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 75% copolymer polycarbonate; 20% silicon copolymer polycarbonate; 3% modified ultra-high molecular weight polysiloxane; 1% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0046] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PCA1105, MI=9g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-25g / 10min, preferably SABIC EXL1414T, MI=9g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.2: 0.3: 0.5; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably benzoyl peroxide from Akzo Nobel, brand Perkadox L-W75.

[0047] The preparation method of the composite material of the present invention:

[0048] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0049] 5. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix evenly, then stir the mixture evenly and let it stand for 4 hours.

[0050] 6. After standing, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0051] 7. After irradiation, the product is extracted and washed with acetone;

[0052] 8. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0053] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0054] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0055] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0056] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0057] project standard Composite material of the present invention Tensile strength MPa GB / T1040 63 Elongation % GB / T1040 71 Bending strength MPa GB / T9341 90 Flexural modulus MPa GB / T9341 2367 Notched impact strength kj / m2 GB / T1843 48 MFRg / 10min GB / T3682 8.4 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.21 Heat Deflection Temperature GB / T1633 125 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV1

[0058] Example 3

[0059] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 70% copolymer polycarbonate; 20% silicon copolymer polycarbonate; 8% modified ultra-high molecular weight polysiloxane; 1% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0060] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PCA1105, MI=9g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-20g / 10min, preferably SABIC EXL1414T, MI=9g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.2: 0.3: 0.5; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably benzoyl peroxide from Akzo Nobel, brand Perkadox L-W75.

[0061] The preparation method of the composite material of the present invention:

[0062] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0063] 9. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix evenly, then stir the mixture evenly and let it stand for 4 hours.

[0064] 10. After standing, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0065] 11. After irradiation, the product is extracted and washed with acetone;

[0066] 12. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0067] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0068] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0069] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0070] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0071] project standard Composite material of the present invention Tensile strength MPa GB / T1040 65 Elongation % GB / T1040 61 Bending strength MPa GB / T9341 93 Flexural modulus MPa GB / T9341 2412 Notched impact strength kj / m2 GB / T1843 44 MFRg / 10min GB / T3682 7.3 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.23 Heat Deflection Temperature GB / T1633 126 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV1

[0072] Implementation Case 4

[0073] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 77% copolymer polycarbonate; 20% silicon copolymer polycarbonate; 1% modified ultra-high molecular weight polysiloxane; 1% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0074] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PCWB2032, MI=3g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-20g / 10min, preferably SABIC EXL1414T, MI=9g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.2: 0.3: 0.5; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably benzoyl peroxide from Akzo Nobel, brand Perkadox L-W75.

[0075] The preparation method of the composite material of the present invention:

[0076] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0077] 13. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix well, then stir the mixture evenly and let it stand for 4 hours.

[0078] 14. After standing, perform irradiation reaction with gamma rays at room temperature and pressure for 30 minutes;

[0079] 15. After irradiation, the product is extracted and washed with acetone;

[0080] 16. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0081] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0082] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0083] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0084] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0085] project standard Composite material of the present invention Tensile strength MPa GB / T1040 62 Elongation % GB / T1040 76 Bending strength MPa GB / T9341 89 Flexural modulus MPa GB / T9341 2332 Notched impact strength kj / m2 GB / T1843 53 MFRg / 10min GB / T3682 3.2 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.20 Heat Deflection Temperature GB / T1633 124 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV1

[0086] Implementation Case 5

[0087] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 77% copolymer polycarbonate; 20% silicon copolymer polycarbonate; 1% modified ultra-high molecular weight polysiloxane; 1% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0088] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PCA1220, MI=20g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-20g / 10min, preferably SABIC EXL1414T, MI=9g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.2: 0.3: 0.5; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably benzoyl peroxide from Akzo Nobel, brand Perkadox L-W75.

[0089] The preparation method of the composite material of the present invention:

[0090] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0091] 17. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate (GMA) and an appropriate amount of initiator into acetone and mix well. Then stir the mixture well and let it stand for 4 hours.

[0092] 18. After standing, perform irradiation reaction with gamma rays at room temperature and pressure for 30 minutes;

[0093] 19. After irradiation, the product is extracted and washed with acetone;

[0094] 20. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0095] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0096] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0097] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0098] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0099] project standard Composite material of the present invention Tensile strength MPa GB / T1040 62 Elongation % GB / T1040 75 Bending strength MPa GB / T9341 89 Flexural modulus MPa GB / T9341 2322 Notched impact strength kj / m2 GB / T1843 49 MFRg / 10min GB / T3682 16.7 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.20 Heat Deflection Temperature GB / T1633 124 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV1

[0100] Implementation Case 6

[0101] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 73% copolymer polycarbonate; 20% silicon copolymer polycarbonate; 3% modified ultra-high molecular weight polysiloxane; 3% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0102] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PCA1105, MI=9g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-20g / 10min, preferably SABIC EXL1414T, MI=9g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.4: 0.8: 1.8; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably Akzo Nobel benzoyl peroxide, brand Perkadox L-W75.

[0103] The preparation method of the composite material of the present invention:

[0104] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0105] 1. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix evenly, then stir the mixture evenly and let it stand for 4 hours.

[0106] 2 After standing still, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0107] 3. After irradiation, the product is extracted and washed with acetone;

[0108] 4. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0109] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0110] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0111] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0112] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0113] project standard Composite material of the present invention Tensile strength MPa GB / T1040 61 Elongation % GB / T1040 72 Bending strength MPa GB / T9341 86 Flexural modulus MPa GB / T9341 2298 Notched impact strength kj / m2 GB / T1843 46 MFRg / 10min GB / T3682 8.5 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.20 Heat Deflection Temperature GB / T1633 124 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV0

[0114] Implementation Case 7

[0115] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 37% copolymer polycarbonate; 60% silicon copolymer polycarbonate; 1% modified ultra-high molecular weight polysiloxane; 1% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0116] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PCA1105, MI=9g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-20g / 10min, preferably SABIC EXL1414T, MI=9g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.2: 0.3: 0.5; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably benzoyl peroxide from Akzo Nobel, brand Perkadox L-W75.

[0117] The preparation method of the composite material of the present invention:

[0118] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0119] 1. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix evenly, then stir the mixture evenly and let it stand for 4 hours.

[0120] 2 After standing still, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0121] 3. After irradiation, the product is extracted and washed with acetone;

[0122] 4. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0123] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0124] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0125] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0126] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0127] project standard Composite material of the present invention Tensile strength MPa GB / T1040 62 Elongation % GB / T1040 88 Bending strength MPa GB / T9341 90 Flexural modulus MPa GB / T9341 2344 Notched impact strength kj / m2 GB / T1843 65 MFRg / 10min GB / T3682 8.3 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.20 Heat Deflection Temperature GB / T1633 124 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV1

[0128] Implementation Case 8

[0129] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 77% copolymer polycarbonate; 20% silicon copolymer polycarbonate; 1% modified ultra-high molecular weight polysiloxane; 1% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0130] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PCA1105, MI=9g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-20g / 10min, preferably Samyang PCST6-3022PJ, MI=5g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.2: 0.3: 0.5; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably benzoyl peroxide from Akzo Nobel, brand Perkadox L-W75.

[0131] The preparation method of the composite material of the present invention:

[0132] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0133] 1. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix evenly, then stir the mixture evenly and let it stand for 4 hours.

[0134] 2 After standing still, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0135] 3. After irradiation, the product is extracted and washed with acetone;

[0136] 4. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0137] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0138] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0139] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0140] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0141] project standard Composite material of the present invention Tensile strength MPa GB / T1040 62 Elongation % GB / T1040 76 Bending strength MPa GB / T9341 89 Flexural modulus MPa GB / T9341 2311 Notched impact strength kj / m2 GB / T1843 50 MFRg / 10min GB / T3682 8.1 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.20 Heat Deflection Temperature GB / T1633 124 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV1

[0142] Implementation Case 9

[0143] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 77% copolymer polycarbonate; 20% silicon copolymer polycarbonate; 1% modified ultra-high molecular weight polysiloxane; 1% compound flame retardant; 0.5% lubricant and 0.5% initiator.

[0144] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PCA1220, MI=20g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-20g / 10min, preferably Samyang PCST4-3022PJ, MI=20g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.2: 0.3: 0.5; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably benzoyl peroxide from Akzo Nobel, brand Perkadox L-W75.

[0145] The preparation method of the composite material of the present invention:

[0146] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0147] 1. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix evenly, then stir the mixture evenly and let it stand for 4 hours.

[0148] 2 After standing still, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0149] 3. After irradiation, the product is extracted and washed with acetone;

[0150] 4. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0151] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0152] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0153] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0154] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0155] project standard Composite material of the present invention Tensile strength MPa GB / T1040 62 Elongation % GB / T1040 74 Bending strength MPa GB / T9341 89 Flexural modulus MPa GB / T9341 2315 Notched impact strength kj / m2 GB / T1843 50 MFRg / 10min GB / T3682 9.4 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.20 Heat Deflection Temperature GB / T1633 124 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV1

[0156] Implementation Case 10

[0157] A method for preparing a novel fluorine-free and halogen-free flame-retardant high-performance PC material, which comprises the following components by weight percentage: 57.7% copolymer polycarbonate; 35% silicon copolymer polycarbonate; 3% modified ultra-high molecular weight polysiloxane; 3% compound flame retardant; 0.3% lubricant and 1% initiator.

[0158] The copolymer polycarbonate is a medium-high viscosity PC with a melt index MI of 3-20g / 10min, preferably Wanhua PC1609T, MI=9g / 10min; the silicon copolymer polycarbonate has a melt index MI=5-20g / 10min, preferably SABIC EXL1414T, MI=9g / 10min; the ultra-high molecular weight polysiloxane has a molecular weight of more than 1 million, preferably Zhejiang Jiahua Jinghua SG-100A; the composite flame retardant is the following three flame retardants added in proportion, including sulfonate flame retardant KSS, organic silsesquioxane flame retardant, and hexaphenoxy cyclotriphosphazene, wherein the sulfonate is preferably Arichem F-535 sulfonate, the silicone flame retardant is preferably Quansheng SIFR-870M, and the hexaphenoxy cyclotriphosphazene is preferably Japan Otsuka SPB-100, the ratio is: F-535: SIFR-870M: SPB-100 = 0.4: 0.8: 1.8; the lubricant is pentaerythritol calcium stearate, preferably PETS-AP from Fuji; the initiator is one of peroxides or azo, preferably Akzo Nobel benzoyl peroxide, brand Perkadox L-W75.

[0159] The preparation method of the composite material of the present invention:

[0160] The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows:

[0161] 1. Add 80-90% by weight of powdered ultra-high molecular weight polysiloxane, 10%-20% of glycidyl methacrylate GMA and an appropriate amount of initiator into acetone and mix evenly, then stir the mixture evenly and let it stand for 4 hours.

[0162] 2 After standing still, irradiate with gamma rays for 30 minutes at room temperature and pressure;

[0163] 3. After irradiation, the product is extracted and washed with acetone;

[0164] 4. After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product.

[0165] Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours;

[0166] Step 3: Add the copolymerized polycarbonate and the silicon copolymerized polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes;

[0167] Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes;

[0168] Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

[0169] project standard Composite material of the present invention Tensile strength MPa GB / T1040 63 Elongation % GB / T1040 72 Bending strength MPa GB / T9341 90 Flexural modulus MPa GB / T9341 2355 Notched impact strength kj / m2 GB / T1843 49 MFRg / 10min GB / T3682 8.6 Shrinkage % GB / T1585 0.5~0.7 Density g / cm3 GB / T1033 1.21 Heat Deflection Temperature GB / T1633 124 Flame retardant UL94 1.6mmV0 Flame retardant UL94 0.8mmV0

Claims

1. A new type of halogen-free and fluorine-free flame-retardant polycarbonate material, characterized in that: It is composed of the following raw materials in percentage by weight:

2. The novel halogen-free and fluorine-free flame-retardant polycarbonate material according to claim 1 is characterized in that: The silicon copolymer polycarbonate has a melt index MI of 5-20 g / 10 min.

3. The novel halogen-free and fluorine-free flame-retardant polycarbonate material according to claim 1 is characterized in that: The copolymer polycarbonate has a melt index MI of 3-20 g / 10 min.

4. The novel halogen-free and fluorine-free flame-retardant polycarbonate material according to claim 1, characterized in that: The modified ultrahigh molecular weight polysiloxane is prepared by using ultrahigh molecular weight polysiloxane powder with a molecular weight of more than 1 million, and then grafting glycidyl methacrylate GMA to the ultrahigh molecular weight polysiloxane through a specific process to prepare a modified ultrahigh molecular weight polysiloxane with a GMA group.

5. The novel halogen-free and fluorine-free flame-retardant polycarbonate material according to claim 1 is characterized in that: The compound flame retardant is a compound of three flame retardants: sulfonate, phosphorus nitrogen and organic silicon.

6. The novel halogen-free and fluorine-free flame-retardant polycarbonate material according to claim 1, characterized in that: The lubricant is pentaerythritol stearate.

7. The novel halogen-free and fluorine-free flame-retardant polycarbonate material according to claim 6, characterized in that: The lubricant is hair-based PETS-AP.

8. The novel halogen-free and fluorine-free flame-retardant polycarbonate material according to claim 1 is characterized in that: The initiator is a peroxide or an azo initiator.

9. The novel halogen-free and fluorine-free flame-retardant polycarbonate material according to claim 1, characterized in that: The initiator is Akzo Nobel Perkadox L-W75.

10. The method for preparing the novel fluorine-free and halogen-free flame-retardant high-performance PC material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The first step is to graft-modify the ultra-high molecular weight polysiloxane to improve its dispersibility, compatibility, reactivity or bridging property in polycarbonate. The implementation method is as follows: (1) Add 80-90% by weight of ultra-high molecular weight polysiloxane powder, 10%-20% of glycidyl methacrylate (GMA) and an appropriate amount of initiator into acetone and mix well. Then stir the mixture and let it stand for 4 hours. (2) After standing, irradiate with gamma rays for 30 minutes at room temperature and pressure; (3) After the irradiation is completed, the product is extracted and washed with acetone; (4) After washing, the mixture was dried at 80°C for 10 hours to obtain a modified ultra-high molecular weight polysiloxane product. Step 2: drying the copolymerized polycarbonate and the silicon copolymerized polycarbonate at 120° C. for 4 hours; Step 3: Add copolymer polycarbonate and silicon copolymer polycarbonate into a high-speed mixer and mix at high speed for 2 to 3 minutes; Step 4: Add the ultra-high molecular weight polysiloxane grafted with GMA, the compounded halogen-free flame retardant, the lubricant, and the initiator into a mixer in proportion and mix for 2-3 minutes; Step 5: extrude the mixed raw materials at high speed through a high torque co-rotating twin-screw extruder with a length-to-diameter ratio of 44:1 and a power of 160KW. The processing temperature of the extruder is set to eleven temperature zones, and the temperature of each temperature zone is 240℃, 260℃, 260℃, 260℃, 250℃, 250℃, 240℃, 240℃, 240℃; the speed is 850r / min, and after twin-screw extrusion according to the above process, a fluorine-free and halogen-free flame-retardant high-performance PC material is obtained.

Citation Information

Patent Citations

  • Flame retardant resin composition

    CN107922736A

  • Impact-resistant halogen-free flame-retardant PC / ABS blend alloy and preparation method thereof

    CN111138824A

  • High-gloss low-filling halogen-free hybrid flame-retardant PC (polycarbonate) material as well as preparation and application thereof

    CN114316561A

  • Phosphorus-containing polysiloxane reactive flame retardant as well as preparation method and application thereof

    CN118772414A

  • Flame-retardant resin composition

    JP2005232442A